2022
DOI: 10.1007/s11095-022-03244-8
|View full text |Cite
|
Sign up to set email alerts
|

Ritonavir-Boosted Exposure of Kinase Inhibitors: an Open Label, Cross-over Pharmacokinetic Proof-of-Concept Trial with Erlotinib

Abstract: Background Although kinase inhibitors (KIs) are generally effective, their use has a large impact on the current health care budget. Dosing strategies to reduce treatment costs are warranted. Boosting pharmacokinetic exposure of KIs metabolized by cytochrome P450 (CYP)3A4 with ritonavir might result in lower doses needed and subsequently reduces treatment costs. This study is a proof-of-concept study to evaluate if the dose of erlotinib can be reduced by co-administration with ritonavir. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In an open-label, crossover study, investigators compared the pharmacokinetics of monotherapy erlotinib 150 mg once daily (control arm) with erlotinib 75 mg daily plus ritonavir 200 mg daily (intervention arm). 51 The authors concluded that the pharmacokinetic exposure at a dose of 75 mg erlotinib when combined with ritonavir was similar to 150 mg erlotinib. In fact, the authors concluded that ritonavir boosting is a promising strategy to reduce erlotinib treatment costs and provides a rationale for other expensive therapies metabolized by CYP 3A4.…”
Section: Discussionmentioning
confidence: 99%
“…In an open-label, crossover study, investigators compared the pharmacokinetics of monotherapy erlotinib 150 mg once daily (control arm) with erlotinib 75 mg daily plus ritonavir 200 mg daily (intervention arm). 51 The authors concluded that the pharmacokinetic exposure at a dose of 75 mg erlotinib when combined with ritonavir was similar to 150 mg erlotinib. In fact, the authors concluded that ritonavir boosting is a promising strategy to reduce erlotinib treatment costs and provides a rationale for other expensive therapies metabolized by CYP 3A4.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 , 35 , 36 , 37 Recently similar pharmacokinetic exposure was shown for a reduced dose of erlotinib with the cytochrome P450 (CYP)3A inhibitor ritonavir compared with the standard erlotinib dose. 18 Several studies are currently ongoing in which the lower equivalent dose of olaparib in combination with the CYP3A inhibitor cobicistat is explored (NCT05078671) and in which ritonavir is used to facilitate the oral administration of docetaxel by increasing bioavailability to reach exposure levels comparable to the intravenous formulation (NCT04028388). A challenge that needs to be acknowledged when pharmacokinetic boosting is the potential interaction with other drugs in the heavily cotreated oncology patient population.…”
Section: Alternative Dosing Regimens Leading To Equivalent Exposurementioning
confidence: 83%
“…Precedent exists for concomitant administration of a drug with another agent that inhibits or induces certain aspect(s) of its disposition pathway to improve systemic exposure, a strategy known as pharmacokinetic boosting. This has been applied to drugs used in the treatment of different diseases such as HIV and cancer [26][27][28][29][30]. Interaction between nitazoxanide and atazanavir/ritonavir has not been reported.…”
Section: Introductionmentioning
confidence: 99%